Effect of Surgical Approach on Node Harvest in Robotic Gastrectomy. Issue 8 (August 2019) - Watson, Michael D.; Trufan, Sally J.; Gower, Nicole L.; Hill, Joshua S.; Salo, Jonathan C.
There has been increasing utilization of minimally invasive surgical approaches. This study evaluates the effect of surgical approach on total lymph node harvest in gastrectomy. Patients undergoing gastrectomy for gastric adenocarcinoma between 2007 and 2018 were reviewed retrospectively. Data collected included age, gender, race, BMI, neoadjuvant therapy, tumor stage, surgical approach, and total number of lymph nodes harvested. The total number of harvested lymph nodes for open, laparoscopic, and robotic gastrectomy was compared using the Kruskal-Wallis test for univariate analysis and a Poisson regression model for multivariable analysis. One hundred four patients were identified. Median node harvest for open, laparoscopic, and robotic approaches were 16, 17, and 36, respectively. Multivariable analysis controlling for gender, BMI, pathological T stage, and year of operation demonstrates that surgical approach is statistically significantly associated with lymph node harvest ( F = 83.4, P < 0.0001). In multivariable analysis, robotic approach was associated with greater lymph node harvest than both open ( P < 0.0001) and laparoscopic ( P < 0.0001) approaches, whereas laparoscopic approach was associated with greater lymph node harvest than open ( P < 0.0001) approach. These data demonstrate that for patients undergoing gastrectomy for gastric adenocarcinoma at our institution, robotic approach is associated with greater lymph node harvest than both laparoscopic and open approaches.